2017
DOI: 10.1159/000476039
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Predicting Bilateral Lymph Node Invasion in High-Risk Prostate Cancer

Abstract: Background: In high-risk prostate cancer (HR-PCA), it is important to consider the factors associated with extensive lymph node invasion (LNI) before planning treatment methods. Objective: To investigate clinical predictors of bilateral LNI in HR-PCA. Materials and Methods: The study evaluated 261 consecutive patients who underwent radical prostatectomy with extended pelvic lymph node dissection. The multivariate multinomial logistic regression model was computed. Results: The high-risk category included 102 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Indeed, the current definition of locally advanced PC includes any patient with positive LNs, regardless of the actual ex- tent of the tumor in the prostatic gland. Recently, high PSA was detected as an independent predictor for LNs invasion in high-risk patients [21] . This clinical variability between patients adds more challenge to the identification of a clear evidence-based approach for the management of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the current definition of locally advanced PC includes any patient with positive LNs, regardless of the actual ex- tent of the tumor in the prostatic gland. Recently, high PSA was detected as an independent predictor for LNs invasion in high-risk patients [21] . This clinical variability between patients adds more challenge to the identification of a clear evidence-based approach for the management of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we previously demonstrated that extensive tumor load at the time of biopsy is a strong predictor of more aggressive PCA in terms of tumor upgrading and upstaging as well as unilateral or bilateral lymph node metastasis and seminal vesical invasion. 3134 Also, we previously found that the number of positive cores can predict tumor upgrading in patients under active surveillance. 35 In this context, PVI, with other clinical parameters, including PSA, DRE and age, should be included in the risk calculator used in the management of patients in which the indication to perform a baseline prostate biopsy is unclear as well as in the prediction of tumor load that is closely related to PCA aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the small sample on patients presenting lymph node involvement in Marcille's fossa, to perform a multivariable analysis was not possible. Moreover, we previously reported our analysis on the clinical predictors of LN invasion in low-, intermediate-and high-risk PCa patients who underwent ePLND [17,34]. 2 (8) 1 ( Aggressiveness of tumour biology associates with multiple LN metastases.…”
Section: Doi: 101159/000500330mentioning
confidence: 99%